RISK MEASUREMENT FOR TRADING ACTIVITIES BASED ON EXPONENTIAL MOVING AVERAGE AND COUNT BACK LINE STRATEGY - Adiratna Anantafortuna, Andhika
Technical analyst traders are trader who make decisions to buy and sell stocks when there is a signal given from the market. These traders identify trends and makes predictions based on patterns in market data. However, after analyzing the losses occurred in the trading activity using Exponential Moving Average and Count Back Line strategy, the losses incurred are much higher than the Jakarta Composite Index’s losses as the benchmark. Thus, using solely sell signal to sell an asset is not limiting the risk faced by technical analyst traders. Value at Risk (VaR) is a popular risk measurement tool that is extensively used to estimate and manage risk. It gives investors an indication of the level of risk they take with a certain investment. Value at Risk can help investors to decide whether the possible gain is worth the potential maximum loss. This final project intends to use Value at Risk as a tool for risk assessment for trading activities based on Exponential Moving Average and Count Back Line strategy. This project also aims to inform the level of risk investors take with a certain investment by calculating the maximum potential loss that occur every day. This final project uses trading activities performed from 1 October to 31 December 2018 based on Exponential Moving Average and Count Back Line strategy as the technical indicator and only limited to stocks listed in IDX30 index. Number of stocks traded using the trading strategy were 27 stocks with 41 transactions in total. Among 41 transactions performed, there were eight trading activities when stocks were traded beyond its Value at Risk limit. The stocks were BBRI (first period), INDF, INTP (first and second period), KLBF, PTPP, SMGR (first period) and WSKT.